2004
DOI: 10.1136/jcp.2004.018051
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mismatch repair proteins, β catenin, and E cadherin in intestinal-type sinonasal adenocarcinoma

Abstract: Background: Despite their histological resemblance to colorectal adenocarcinomas, there is little information about the molecular events involved in the pathogenesis of intestinal-type sinonasal adenocarcinomas (ITACs). Aims: To evaluate the possible role of DNA mismatch repair (MMR) gene defects or disruptions of the E cadherin-b catenin complex in ITAC by investigating the immunohistochemical expression of the MMR gene products, b catenin, and E cadherin in a group of sporadic ITACs. Methods: Ten sporadic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
37
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 24 publications
(28 reference statements)
6
37
1
Order By: Relevance
“…The absence of nuclear β-catenin staining is in line with Perez Ordonez et al who found only membranous staining in all ten analyzed cases of ITAC [26]. However in one study, eight of 20 cases (40%) showed membranous, cytoplasmic and nuclear positivity [10].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The absence of nuclear β-catenin staining is in line with Perez Ordonez et al who found only membranous staining in all ten analyzed cases of ITAC [26]. However in one study, eight of 20 cases (40%) showed membranous, cytoplasmic and nuclear positivity [10].…”
Section: Discussionsupporting
confidence: 88%
“…Mutations in TP53, with a frequency of 60%-70% in CRC, ranged between 18% and 57% in ITAC [10,33,34], and 50% of loss of heterozygosity was detected at 17p13, the chromosomal locus of TP53 [27]. Other genetic alterations known in CRC, such as APC, β-catenin, p16 and mismatch repair genes were absent in ITAC [10,26,35]. Aiming for a genome-wide view of recurrent genetic abnormalities, CGH (Comparative Genomic Hybridization) and microarray CGH analysis have been performed and revealed frequent gains on chromosome arms 5p, 7q, 8q, 12p, and 20q, and losses on 4, 5q, 8p, 17p and 18q [2,11,17].…”
Section: Introductionmentioning
confidence: 98%
“…11 Further attempts to find genetic alterations as described in colorectal adenocarcinoma concerned APC, b-catenin, and various mismatch repair genes gave negative results. 10,15,17 These results indicate that ITAC and colorectal adenocarcinoma have different genetic pathways of development and progression.…”
mentioning
confidence: 89%
“…The preserved nuclear expression of MLH1, MSH2, MSH3, and MSH6 suggested that mutations or promoter methylation of MMR genes do not play a role in the pathogenesis of ITAC [42]. …”
Section: Discussionmentioning
confidence: 99%